On the Self-serving Use of Equity Principles in International Climate Negotiations - Andreas Lange; Andreas Löschel; Carsten Vogt; Andreas Ziegler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This paper puts forward equity as an important structural element to understanding negotiation outcomes. We first advance bargaining theory to incorporate the self-serving use of equity. Agents are predicted to push equity principles which benefit them more than other parties, in particular those which are disadvantageous to parties with large bargaining power. Based on unique data from a world-wide survey of agents involved in international climate policy, we then study how participants assess the support of the equity criteria by major parties in the climate negotiations. Comparing these results with cost estimates from a POLES model, we find that the perceived equity preferences of the respective countries or groups of countries are in general consistent with our hypothesis of a self-serving use of equity criteria and thereby lend support for our theoretical model. While this self-interest is recognized by the participants of our survey for the positions of the USA and the G77/China as well as Russia, the EU manages to be seen as choosing (self-serving) equity arguments out of fairness concerns and in order to facilitate the negotiations.
Keywords: H41; D63; C7; 330; bargaining theory; equity criteria; self-serving bias; climate policy; survey data